Caracterização e identificação de vírus em allium spp - Bampi, Daiana [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The genus Allium includes important species used for human consumption, as garlic,onion and many other species grown as ornamentals. Some of these species are propagated vegetatively and can be infected by viruses belonging to the genera Allexivirus, Carlavirus and Potyvirus, often in mixed infections. Leek yellow stripe virus (LYSV) belongs to the genus Potyvirus and is considered the most important virus in Allium species. The complete genomic sequence of Leek yellow stripe virus garlic isolate from Brazil (LYSV-MG) has been determined. The LYSV-MG genome consists of 10,341 nucleotides and encodes a deduced polyprotein of 3,221 amino acids. Based on the analysis of the coding region for P1 protein, isolate LYSV-MG and others collected in garlic producing regions, could not be classified as belonging to the groups S and N. Brazilian isolates do not have the deletion present in the P1 from the S-type group but are more closely related to S-type than to N-type isolates. The Brazilian isolates formed a monophyletic group closer to S-type and one isolate from Okinawa, Japan. Brazilian isolates share 97-99% of P1 region nucleotide identity with each other, and 51-64% with different isolates from around the world. The data suggest that Brazilian LYSV isolates are derived from an ancestral source of the Okinawa and S-type isolates, prior to the P1 deletion and divergence in the S-type isolates. As part of the doctorate sandwich in United States Department of Agriculture, under the supervision of Dr. John Hammond, viruses present in ornamental Allium from Beltsville, MD were detected. Bulbs of fourteen different species of Allium were purchased from retail nurseries and planted in the field during the fall of 2013. Leaf tissue from the flowering symptomatic plants were collected during spring 2014, and tested by PCR using generic primers for the genus Allexivirus, Carlavirus and Potyvirus. PCR-positive ...

O gênero Allium inclui espécies de importância para o consumo humano como o alho, cebola e espécies ornamentais. Algumas destas espécies por serem propagadas vegetativamente, podem ser infectadas por vírus pertencentes aos gêneros Allexivirus, Carlavirus e Potyvirus, frequentemente em infecções mistas. Leek yellow stripe virus (LYSV) pertence ao gênero Potyvirus e é considerada a espécie de maior importância na cultura do alho, de modo que foi sequenciado o genoma completo de um isolado de LYSV brasileiro (LYSV-MG) e avaliada sua diversidade genética. Seu genoma possui 10.341 nucleotídeos e codifica uma poliproteína de 3221 aminoácidos. Baseado na análise da região codificadora para a proteína P1, o isolado LYSV-MG, bem como demais coletados em regiões produtoras de alho, não foram classificados como pertencentes aos grupos S e N. Os isolados brasileiros apesar de não apresentarem a deleção na região da P1 (típica do grupo S), formaram um grupo monofilético muito próximo deste grupo e de um isolado de Okinawa, Japão. Em relação ao gene P1, os isolados brasileiros compartilharam 97-99% de identidade de nucleotídeos entre si e 51-64% com isolados de LYSV de outros países. Os dados sugerem que os isolados brasileiros de LYSV, o isolado de Okinawa e os isolados pertencentes ao grupo S podem ser provenientes de um ancestral comum antes da ocorrência da deleção na P1 e divergência dos isolados no grupo S. Como parte do doutoramento sanduíche, realizado na United States Department of Agriculture, sob orientação do Dr. John Hammond, foram estudados os vírus presentes em quatorze diferentes espécies de Allium ornamental nos Estados Unidos. As plantas foram adquiridas em floriculturas e plantadas a campo no outono de 2013 na região de Beltsville, MD. Folhas sintomáticas foram coletadas após a floração durante a primavera de 2014 e avaliadas por PCR usando primers ...
Characterization and identification of virus in allium spp
Keywords: Alho - Cultivo; Alho - Doenças e pragas; Viroses das plantas; Garlic